2005
DOI: 10.1007/s00170-004-2280-7
|View full text |Cite
|
Sign up to set email alerts
|

Drilling of uni-directional glass fiber reinforced plastic (UD-GFRP) composite laminates

Abstract: Drilling of fiber reinforced plastic (FRP) composite materials is a field open to a plethora of questions. Drillinginduced damage is a research area that has not been explored exhaustively. The present research endeavor is an effort to correlate drilling-induced damage with drilling parameters. Tool point geometry is considered a major factor that influences drillinginduced damage. Experiments were conducted and drillinginduced damage was quantified using the digital image processing technique. The results als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 14 publications
1
69
0
Order By: Relevance
“…Components made from CFRP composites are mostly produced in near-net-shape. However, secondary manufacturing processes such as milling and drilling are often required for imparting the dimensional tolerances and assembly of composite parts [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Components made from CFRP composites are mostly produced in near-net-shape. However, secondary manufacturing processes such as milling and drilling are often required for imparting the dimensional tolerances and assembly of composite parts [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This is because, high coolant pressure gives a higher coolant flow rate, which reduces the drill temperature more effectively and thereby reduces the workpiece damage factor. Singh and Bhatnagar [22] have reported that drill induced damage is maximum at higher cutting speeds and Paulo Davim et al [8] have reported that drill induced damage is maximum at higher feeds in laminated GFRPs. Similar results are observed in nonlaminated GFRE composites having 08 fibre orientations with respect to the drill, in the present study.…”
Section: Resultsmentioning
confidence: 98%
“…The experiments were designed by applying RSM with selected cutting conditions [22]. The selection of the spindle speed and feed was based on the usual parameter levels found in related literature and also a r c h i v e s o f c i v i l a n d m e c h a n i c a l e n g i n e e r i n g x x x ( 2 0 1 5 ) x x x -x x x from the manufacturer's recommendations, besides the required homogenization of the parameters considered for an adequate comparison [28].…”
Section: Plan Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the core drill offers the highest critical feed rate followed by candle stick drill, saw drill, step drill and the traditional twist drill. The mathematical models to predict the thrust force, torque and delamination during drilling of composite laminates have also been developed [21,22]. Various predictive models have been developed, but the need of the hour is to develop more generic models is an area of paramount importance.…”
Section: Introductionmentioning
confidence: 99%